Study on the potential of airships as urban mass public transport in Malaysia - Aminian, Negin O.; Romli, Fairuz I. (Universiti Teknologi MARA (UiTM), Malaysia, 2017)
Transportation capability is an essential need in progressing and improving the quality of lifestyle for a society to a better level. In many urban cities, traffic congestion problems have always been a big issue and despite several efforts made to alleviate the situation, the problem still remains. Taking cue from the proposal of a personal flying car to overcome traffic congestion, a concept of "flying bus" using airships is proposed in this study as a new public transport option within urban areas. To highlight the potential of this idea, particularly for Kuala Lumpur city areas in Malaysia, a comparison analysis between the available public transportation options is done along with the new proposed concept using Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. Two case studies have been formulated for the comparison analysis, which is assessed in five different evaluation scenarios to capture the robustness of the results. All in all, it is found that the proposed "flying bus" concept does have some advantages over other public transport options and its implementation can be beneficial to improve the public transportation service for the society within the Kuala Lumpur city areas.